2022-RA-367-ESGO Rucaparib in clinical practice – what are the elements of patient adherence?. (20th October 2022) - Braicu, Elena-Ioana; Halwani, Zaher; Zocholl, Dario; Dysarz, Jessica; Enzinger, Hans-Martin; Hamann, Moritz; Peters, Martin; Forstbauer, Helmut; Busch, Steffi; Sehouli, Jalid
Abstract : Introduction/Background: Every year, around 127, 634 women in Europe are diagnosed with ovarian cancer (OC). The majority of the patients detected are diagnosed in advanced stages due to lack or unspecific symptoms and/or no effective screening methods. Hence prognosis is poor. Although most of the patients will be in complete remission following primary cytoreduction and platinum-based chemotherapy, half of the advanced ovarian cancer patients will experience relapse within two years after the diagnosis. In the recurrent therapy option, PARP became a new target in ovarian cancer. Maintenance with PARP inhibitors significantly improved progression free survival in both primary and relapsed high grade ovarian cancer. We have previously investigated patients' preferences and expectations from cancer maintenance treatment regimens (Expression IV project). The results from this project indicated that patients choose maintenance therapy primarily to improve the therapeutic outcome and secondarily to improve their quality of life. Based on these results, we considered to perform a fully prospective study characterizing the real-world adherence and progression-free-survival time (PFS), as there is currently limited information available about the adherence to novel therapies such as rucaparib. Methodology: This study will recruit 150 patients with histologically diagnosed platinum-sensitive relapsed high grade ovarian cancer, fallopian tube cancer, or primary peritoneal cancer, that are eligible for rucaparib maintenance therapy according to Summary of Product Characteristics (SmPC). Throughout the study, individual patient data will be collected at baseline and every three months until disease progression or patient's death whichever occurs first. To capture adherence to rucaparib therapy an adaption (according to the rucaparib therapy) of the 'Essener Compliance Score' (ECS) is used. As of June 2022, 13 patients have been included in this study. Results: / Conclusion: /